Aging of Rejuvenated Asphalt Binders - Mojtaba Mohammadafzali; Hesham Ali; James A. Musselman; Gregory A. Sholar; Wayne A. Rilko (Advances in Materials Science and Engineering)
An important concern that limits the RAP content in asphalt mixtures is the fact that the aged binder that is present in the RAP can cause premature cracking. Rejuvenators are frequently added to high RAP mixtures to enhance the properties of the binder. There is no existing method to predict the longevity of a rejuvenated asphalt. This study investigated the aging of rejuvenated binders and compared their durability with that of virgin asphalt. Various samples with different types and proportions of RAP, virgin binder, and rejuvenator were aged by RTFO and three cycles of PAV. DSR and BBR tests were conducted to examine the high-temperature and low-temperature rheological properties of binders. Results indicated that the type and dosage of the rejuvenator have a great influence on the aging rate and durability of the binder. Some rejuvenators make the binder age slower, while others accelerate aging. These observations confirm the importance of evaluating the long-term aging of recycled binders. For this purpose, critical PAV time was proposed as a measure of binder’s longevity.